Multiplayer Chess Game Development Using Augmented Reality and 3D Models - Cerron, Fredy (2023)
The principal aim of this project was to innovate the classic board game chess so people can play at any time and place without the need for physical space and real pieces for the game to run correctly. This project can encourage more people to become interested in this board game by using augmented reality technology and personalized models and animations. Players can use the application without the need to use a physical board or pieces and without any kind of image marker. They just need to point at a flat surface with the phone camera so that all the game objects appear and then they can interact with the game intuitively by selecting the elements on the screen. The system has been created to work on high-end Android phones using the technology of Unity and Vuforia.